NMPC controller applied to an UAV Path Following Problem - Santa Maria, Tiago Henrique; Pusssente, Guilherme Augusto; Marcato, André Luís; de Aguiar, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Nowadays, UAVs are used in several industrial applications so indoors and outdoors environments. The main objective of this paper is to propose a control strategy applied to UAVs using line-following and computer vision. In this way, this paper presents a Non-linear Model Predictive Control (NMPC) combined with a PID controller aiming to provide smooth control actions. To evaluate the model robustness, the authors perform simulations in environments containing ﬂaws in the visual segments. The control scheme presented in this paper has a better performance when compared to the NMPC standalone or classic control strategies such as PID.